Myxomycete biodiversity on five islands of the Seychelles - Kryvomaz, Tetiana; Michaud, Alain; Stephenson, Steven L. (Zootaxa, 2020)
A survey of myxomycete diversity on five islands of the Seychelles yielded 105 species and 10 infra-specific taxa, which included 89 species on La Digue, 66 on Praslin, 63 on Mahé, 31 on Curieuse and 4 on Félicité. Among these records, 64 species are new for the Seychelles and together with data from the literature, 143 species of myxomycetes are now known for all of the Seychelles. Most collecting on all five islands was carried out in low elevation areas. Forty-four species (73% of all specimens of myxomycetes) were found in low-elevation localities, and among these were Arcyria helvetica, Dictydiaethalium dictyosporum, Echinostelium paucifilum, Physarum aeneum, Ph. echinosporum, Reticularia olivacea, and Stemonaria longa. From 54 species of plants used by myxomycetes as substrates, eight species provided 63% of the specimens of myxomycetes, with most samples recorded from Calophyllum inophyllum. On the basis of substrate type, myxomycetes were distributed as follows: 37% of specimens were collected on dead wood and decaying palm stems, 16% on the bark and stems of living plants, 25% on ground litter, and 22% on aerial litter. A comparison of the assemblages of myxomycetes found in zones with different levels of human impact indicated that 84 species were found in forests, 74 in anthropogenic areas, and 62 in recreational coastal areas. The Seychelles provide a good background for a high level of myxomycete diversity, as a consequence of favorable climatic conditions and their location between Asia and Africa.